Development of control system for critical parameters of medical device sterization at an electron accelerator - Pomatsalyuk, R.I.; Shevchenko, V.A.; Shlyakhov, I.N.; Tenishev, A.Eh.; Uvarov, V.L. (Вопросы атомной науки и техники, 2015)
The hard- and software interfaces that provide on-line control and archiving of the basic parameters of the medical device sterilization (electron energy, beam current, width and shape of the beam scan, the conveyor speed and the absorbed dose in the treated products) have been developed at a radiation-industrial installation LU-10 of NSC KIPT. The main primary sensor of the control system is a stack-type monitor-absorber of the beam located behind the line of movement of the processed objects. Continuous monitoring of the processing parameters is performed by measuring and analyzing the currents from the plates of the monitor in a mode of "radiation shadow" created by irradiated objects. The structure of the control system, how it works and the calibration procedures for measuring channels are described. Для системи управління радіаційно-технологічною установкою ЛУ-10 ННЦ ХФТИ розроблені приладовий і програмний інтерфейси, що забезпечують on-line контроль і архівацію основних параметрів процесу стерилізації продукції медичного призначення – енергії електронів, струму пучка, ширини і форми його розгортки, а також швидкості конвеєра і поглинутої дози в оброблюваних виробах. Основним первинним перетворювачем системи контролю є пластинчатий монітор-поглинач пучка, розміщений за лінією переміщення оброблюваних об'єктів. Безперервний моніторинг параметрів обробки проводиться шляхом вимірювання і аналізу струмів з пластин монітора в режимі створюваної об'єктами «радіаційної тіні». Описано структуру системи контролю, принцип її роботи і процедуру калібрування вимірювальних каналів. Для системы управления радиационно-технологической установки ЛУ-10 ННЦ ХФТИ разработаны приборный и программный интерфейсы, обеспечивающие on-line контроль и архивирование основных параметров процесса стерилизации изделий медицинского назначения – энергии электронов, тока пучка, ширины и формы его развертки, а также скорости конвейера и поглощенной дозы в обрабатываемых изделиях. Основным первичным преобразователем системы контроля является пластинчатый монитор-поглотитель пучка, размещенный за линией перемещения обрабатываемых объектов. Непрерывный мониторинг параметров обработки производится путем анализа токов с пластин монитора в режиме создаваемой объектами «радиационной тени». Описаны структура системы контроля, принцип ее работы и процедура калибровки измерительных каналов.